Lessons learned : a guide to improved aircraft design - Nicolai, Leland M. (American Institute Of Aeronautics and Astronautics, 2016)
Lessons Learned: A Guide to Improved Aircraft Design features a lifetime of practical insight into the aspects of aircraft design that cannot be solved via technical means. The lessons learned have nothing to do with the mechanics of doing conceptual design, rather they address and influence the design team's state of mind and the human principles to be used when dealing with the customer. It is a concise, informative summary of mistakes to avoid, and best practices to pursue, that lead to successful aircraft design programs.
Keywords: Airplanes -- Design and construction.; Aeronautics -- Safety measures.; elektronické knihy; electronic books